2015
DOI: 10.3390/molecules20046544
|View full text |Cite
|
Sign up to set email alerts
|

Longevity Extension by Phytochemicals

Abstract: Phytochemicals are structurally diverse secondary metabolites synthesized by plants and also by non-pathogenic endophytic microorganisms living within plants. Phytochemicals help plants to survive environmental stresses, protect plants from microbial infections and environmental pollutants, provide them with a defense from herbivorous organisms and attract natural predators of such organisms, as well as lure pollinators and other symbiotes of these plants. In addition, many phytochemicals can extend longevity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 161 publications
(383 reference statements)
0
63
0
Order By: Relevance
“…Plants produce phytochemicals for survival, ecosystem adaptation, and defence when faced with environmental stress and infection by pathogenic organisms (Leonov et al 2015;Shah et al 2015). This suggests that for A. caudatus grown with AgNPs to tolerate the stress imposed by reconditioning the soil habitat due to the introduction of nanoparticles, it generated more phytochemicals for its survival and defence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Plants produce phytochemicals for survival, ecosystem adaptation, and defence when faced with environmental stress and infection by pathogenic organisms (Leonov et al 2015;Shah et al 2015). This suggests that for A. caudatus grown with AgNPs to tolerate the stress imposed by reconditioning the soil habitat due to the introduction of nanoparticles, it generated more phytochemicals for its survival and defence.…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemicals have been reported to offer protection against cancer, cardiovascular diseases and diabetes due to their anti-cancer, anti-inflammatory, and anti-diabetic properties (Chandra et al 2014;Leonov et al 2015). Epidemiological studies have also strongly shown that consumption of vegetables positively correlated to prevention of degenerative diseases (Li et al 2015), while studies have established high correlation between antioxidant activity and phytochemicals of vegetables (Olajire and Azeez 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the models, for longevity of human organisms are phytochemicals derived from plants. Phytochemicals may be from different classes: phenolic compounds, terpenes, polysulfides, quinones and polyamines (Leonov et al, 2015). One of the phytochemicals bioactive compounds that influence the human aging, is stilbene phytoalexin transresveratrol (trans-3,4′,5-trihydroxystilbene) ( (Fig.…”
Section: Introductionmentioning
confidence: 99%